Amoebic peritonitis in pregnancy in the United Kingdom. Issue 740 (June 1987) - Constantine, G.; Menon, V.; Luesley, D.
Abstract : We describe a woman who developed hepatic amoebic abscesses during pregnancy, and subsequently amoebic peritonitis. We believe this to be the first such recorded case in the United Kingdom, and unusual in that the patient had never been abroad.